Le droit des valeurs mobilières et les placements privés - Antaki, Nabil; Leclerc, Gilles (Les Cahiers de droit, 1979)
The overwhelming control of the different North American securities commissions over the capital market compels businessmen and corporate lawyers to a permanent search for new means to avoid the registration and prospectus requirements of the acts. The authors try in this article to analyse the private placement exemption which seems to be most frequently relied upon. They discuss its development since the United States Supreme Court's decision in Ralston Purina. They explain the pros and cons of the subjective « need to know » and the capability of investors to « fend for themselves » tests as well as their byproducts. The recent and certainly more objective standards adopted by the S.E.C. and Ontario are also discussed. Finally, the resale of the restricted securities acquired in a private placement transaction is studied. In this context, the Quebec law is hardly adequate and needs substantial clarifications.